2012
DOI: 10.1021/nl301937j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Single-Nanoparticle Surface-Chemistry by Plasmonic Overheating in an Optical Trap

Abstract: Surface-chemistry of individual, optically trapped plasmonic nanoparticles is modified and accelerated by plasmonic overheating. Depending on the optical trapping power, gold nanorods can exhibit red-shifts of their plasmon resonance (i.e. increasing aspect ratio) under oxidative conditions. In contrast, in bulk exclusively blue shifts (decreasing aspect ratios) are observed. Supported by calculations, we explain this finding by local temperatures in the trap exceeding the boiling point of the solvent which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
(58 reference statements)
1
35
0
Order By: Relevance
“…However, several studies have shown that heating can be controlled and in some cases even taken advantage of. 125 129 and nanolithography of polymers based on curing or milling processes. [131][132] Temperature measurements at the nanoscale are experimentally challenging.…”
Section: Heating Of Optically Trapped Metal Colloidsmentioning
confidence: 99%
“…However, several studies have shown that heating can be controlled and in some cases even taken advantage of. 125 129 and nanolithography of polymers based on curing or milling processes. [131][132] Temperature measurements at the nanoscale are experimentally challenging.…”
Section: Heating Of Optically Trapped Metal Colloidsmentioning
confidence: 99%
“…Ni et al showed that optically trapped gold nanorods in an oxidizing environment undergo a temperature dependent anisotropic etching process. 74 At low trapping powers (surface temperatures) the trapped nanorods are preferentially etched from their tips since the denser ligand coverage protects the sidewalls. This is the same behaviour as observed in bulk colloidal solutions.…”
Section: Local Heatingmentioning
confidence: 99%
“…Trapping of micron and submicron sized particles have received significant attention in several branches of science including biotechnology 13 , physics 4 , and chemistry 5 . Optical trapping and manipulation schemes are playing an important role in the operation of lab-on-a-chip (LOC) devices 6 .…”
Section: Introductionmentioning
confidence: 99%